Investigation of Solid-State Hydrate-Anhydrous Phase Transformations of Dabigatran Etexilate Hemi-Edisylate - Feng, Jin; Lim, Changjin; Nam, Sihyun; Yoon, Woojin; Yun, Hoseop; Kim, Woo Sik; An, Ji Hun (Crystals, 2023)
In this study, a dabigatran etexilate edisylate (DBE) was prepared by the reaction crystallization of dabigatran etexilate (DBG) and edisilic acid. According to single crystal X-ray diffraction (SXRD), it was revealed that two DGB were combined with one edisylate and associated with one water for DBE monohydrate. Additionally, the hot stage microscopy showed that the DBE monohydrate was transformed to DBE amorphous solid and then finally shifted to the DBE anhydrate in solid-state. Using powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and a hygroscopic test, it was confirmed that the phase transformation of DBE monohydrate to DBE anhydrate was irreversible. Additionally, any other crystal form of DBE anhydrate was not available because it was the most stable phase.
Keywords: crystal structure; dabigatran etexilate; polymorphic transformation; polymorphs; salt form